The importance of using quality indicators in nursing care - Thaizy Valânia Lopes Silveira; Pedro Paulo do Prado Júnior; Andréia Guerra Siman; Marilane de Oliveira Fani Amaro
OBJECTIVE: To investigate the opinion of hospital nurses on the use of quality indicators for nursing care. METHOD: Research based on the qualitative approach, conducted with 41 nurses from two charity hospitals in Minas Gerais, from September to October 2013. Interviews with a semi-structured script were used to collect data. The empirical data were organized by means of content analysis. RESULTS: Indicators are important for assessing the provided care, for improving the quality of care, and for defining strategies to achieve goals. CONCLUSIONS: The difficulties encountered when using these indicators revealed the following constituent elements: lack of time, inadequate number of professionals and lack of knowledge on the subject. It was concluded that nurses understand that indicators are instruments that enable evaluations and improvements, but their understanding of how to use these instruments is incomplete and fragmented.